Molecular detection, epidemiology and clinico-pathological studies on first outbreak of porcine reproductive and respiratory syndrome (PRRS) in pig population of Mizoram, India - RAJKHOWA, T K; GOGOI, A; HAUHNAR, L; ISAAC, I (The Indian Journal of Animal Sciences, 2015)
Porcine reproductive and respiratory syndrome (PRRS), an economically important viral disease of the pig industry worldwide, has brought great losses to the Chinese pig production in recent years, particularly following the emergence of the highly pathogenic PRRS virus (PRRSV). The Government of India has reported the first outbreak of the disease in pig population of Mizoram to OIE on 26 June 2013.The present study was carried out on molecular detection, epidemiology and clinico-pathological studies of the outbreak. Studies on 880 pigs revealed 65% morbidity and 63.11% mortality with highest mortality rate in pre-weaned piglets (81.06%) followed by pregnant sows (68%). Histopathological examination showed severe interstitial pneumonia and lymphoid depletion in the lymphoid organs. Diagnosis of the disease was confirmed by RT-PCR on tissue samples targeting the ORF-4 and ORF-7 genes of PRRSV. Sequencing of the amplified products revealed that the PRRSV detected in Mizoram belongs to the genotype II (North American type).